The effects of group dynamics activities on the self-concepts of Thai students - Nanthana Wong-in 1948-
The purpose of the study is to determine the effects of group dynamics activities on the self-concept of freshman students in Petchburee Withayalongkorn Teacher Village, Thailand. The study reveals that dynamics activities affect the students' self-concepts and the four aspects of the self-concept can be improved through the activities.